Disentangling Sedimentary Pathways for the Pleniglacial Lower Danube Loess Based on Geochemical Signatures - Pötter, Stephan; Veres, Daniel; Baykal, Yunus; Nett, Janina J.; Schulte, Philipp; Hambach, Ulrich; Lehmkuhl, Frank (Frontiers in Earth Science, 2021)
The source of aeolian sediments such as loess has been investigated since decades. Reliable knowledge on potential dust sources is crucial to understand past climatic and environmental conditions accompanying the dispersal of early modern humans (EMH) into Europe. Provenance studies are usually performed on small sample sets, and most established methods in provenance studies are expensive and time-consuming. Here, we present the results of high-resolution geochemical analyses performed on five loess-palaeosol sequences from the Lower Danube Basin (LDB), a region, despite its importance as a trajectory for EMH, largely underrepresented in loess provenance studies. We compare our results with geochemical data of loess-palaeosol sequences from Austria, Hungary, Serbia, and Ukraine. Based on published literature, we thus evaluate five plausible sedimentary pathways for the LDB loess: (1) the Danube alluvium (DA) pathway, which constrains the transport and re-deposition of detrital material by the Danube and its tributaries; (2) the Carpathian Bending (CB) pathway, where sediment is mainly transported from the Cretaceous to Neogene flysch of the Eastern Carpathian Bending; (3) the Eastern Carpathian (EC) pathway, in which sediment is eroded from the flysch of the Outer Eastern Carpathians, transported by rivers, and deflated by northwesterly to westerly winds; (4) the glaciofluvial (GF) pathway, where dust is deflated from glacial outwash plains in nowadays Ukraine, and (5) the Black Sea (BS) pathway, where dust originates from the exposed shelf of the Black Sea. Based on geochemical data, we consider the DA pathway to be the major sediment trajectory for loess in the LDB. Especially the sequences located close to the Danube and the Dobrogea show similarities to sites in Central and Northeast Hungary as well as Northern Serbia. For the northeastern part of the LDB, we demonstrate that dust input is mainly sourced from primary material from the Eastern Carpathians. Mineralogical estimations and geochemical data render the CB pathway as an additional substantial source of detrital material for the loess of this area. We consider the influence of the GF pathway in the LDB as negligible, whereas some minor influences of the BS pathway cannot be ruled out based on geochemical data.